Scenario based risk management for Arctic shipping and operations - Ehlers, S; Kujala, P; Veitch, B; Faisal Khan; Vanhatalo, J (2014)
Arctic oil and gas explorations and Arctic shipping must ensure the safety and protection of this sensitive environment in spite of the challenging operational conditions. However, current regulations and assessment methods do not predict the associated risk level reliably. In other words, ships transiting ice-covered waters are not designed according to physical measures, such as accurate limit states under ice loading, but according to economic and empirical design measures. Similarly, offshore installations should be designed according to the accurate limit states, but the actual ice loads are uncertain so this is not possible at present. Risk-based design methodologies using first principal methods offer a way to advance safe operations and transport of natural resources within and out of the Arctic Sea. This paper introduces a holistic treatment of the design relevant features and their identification to improve safe Arctic operations and transport. The focus is on design relevant Arctic aspects related to extreme and accidental ice events. The approach includes estimating ice loads, including extreme load events, assessing structural consequences of the loading events, assessing associated potential environmental consequences, and establishing a risk based design framework for managing risks. Copyright Â© 2014 by ASME.